The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/aac.47.10.3311-3317.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tylosin on Bacterial Mucolysis, Clostridium perfringens Colonization, and Intestinal Barrier Function in a Chick Model of Necrotic Enteritis

Abstract: Necrotic enteritis (NE) is a worldwide poultry disease caused by the alpha toxin-producing bacterium Clostridium perfringens. Disease risk factors include concurrent coccidial infection and the dietary use of cereal grains high in nonstarch polysaccharides (NSP), such as wheat, barley, rye, and oats. Outbreaks of NE can be prevented or treated by the use of in-feed antibiotics. However, the current debate regarding the prophylactic use of antibiotics in animal diets necessitates a better understanding of facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 34 publications
2
49
0
4
Order By: Relevance
“…The counts of C. perfringens in luminal contents from the ileum and caeca of birds fed the PC diet were as low as 3-4 log 10 cfu/g digesta on both sampling days, indicating that the IFAs used in the present study were highly effective in controlling C. perfringens proliferation in the gut of broilers. These findings are consistent with previous studies of the culture-based and molecular studies, which demonstrated that dietary supplementation with antibiotics such as Zn-bacitracin, bacitracin methylene disalicylate and tylosin causes a significant reduction in lesion scores and mortality caused by NE (Brennan et al 2003;Collier et al 2003).…”
Section: Ileal and Caecal Microflorasupporting
confidence: 82%
See 1 more Smart Citation
“…The counts of C. perfringens in luminal contents from the ileum and caeca of birds fed the PC diet were as low as 3-4 log 10 cfu/g digesta on both sampling days, indicating that the IFAs used in the present study were highly effective in controlling C. perfringens proliferation in the gut of broilers. These findings are consistent with previous studies of the culture-based and molecular studies, which demonstrated that dietary supplementation with antibiotics such as Zn-bacitracin, bacitracin methylene disalicylate and tylosin causes a significant reduction in lesion scores and mortality caused by NE (Brennan et al 2003;Collier et al 2003).…”
Section: Ileal and Caecal Microflorasupporting
confidence: 82%
“…A variety of in-feed antibiotics (IFAs), including virginiamycin, bacitracin, penicillin and tylosin, have been used in feed to effectively control and prevent NE (Watkins et al 1997;Collier et al 2003). However, many countries are moving towards a reduction in the use of IFAs in animal diets because large-scale use of antibiotics can cause resistant bacterial strains to develop (Barton 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was hypothesized that the number of total acidic mucin-containing goblet cells may have been elevated in the C. perfringens-challenged chickens because of protective properties against pathogens of acidomucin (Conour et al, 2002), and high bacterial populations have been associated with increased secretion of sulphomucins (Robertson & Wright, 1997). However, C. perfringens was reported to possess 13 hydrolase families predicted to be involved in mucin glycoprotein breakdown (Ficko-Blean & Boraston, 2006) and had significant acidomucolytic potential and grew rapidly on mucincontaining medium (Deplancke et al, 2002), which suggested that C. perfringens may be particularly mucolytic and its growth would be favoured by the increased host mucous production (Collier et al, 2003(Collier et al, , 2008. Our current study indicated C. perfringens challenge reduced acidomucin and sulfomucin goblet cell density in the ileum villi, which is not in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The disease causes severe necrosis of the intestinal tract, disrupts villusÁcrypt micro-architecture, and increases intestinal permeability and translocation of intestinal bacteria, thus compromising the integrity of mucosal barrier function (Collier et al, 2003(Collier et al, , 2008Liu et al, 2010;Golder et al, 2011) and lowering nutrient absorption and bird performance (Xu et al, 2003;Jia et al, 2009). The major factors for NE are the proliferation of the enteric bacterium Clostridium perfringens type A or C and production of exotoxins (Keyburn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although many C. perfringens poultry isolates appear to be resistant against bacitracin (Kondo, 1988;Devriese et al, 1993;Watkins et al, 1997), inclusion of this agent in broiler feed reduced intestinal C. perfringens counts, the number of gut lesions, lesion scores and mortality caused by necrotic enteritis in challenge experiments and field trials (Prescott, 1979;Stutz et al, 1983;Stutz & Lawton, 1984;Broussard et al, 1986;Engberg et al, 2000;Lovland et al, 2003;Brennan et al, 2003;Jackson et al, 2003). Also multiple studies showed that tylosin (Stutz & Lawton, 1984;Vissiennon et al, 2000;Brennan et al, 2001;Collier et al, 2003) and virginiamycin (George et al, 1982;Stutz & Lawton, 1984) inclusion in broiler feed reduced the occurrence of and mortality due to necrotic enteritis, and the intestinal counts of C. perfringens.…”
Section: Growth-promoting Antibioticsmentioning
confidence: 99%